H2S‐Mediated Thermal and Photochemical Methane Activation. Issue 17 (22nd October 2013) - Baltrusaitis, Jonas; de Graaf, Coen; Broer, Ria; Patterson, Eric V.
Abstract Sustainable, low‐temperature methods for natural gas activation are critical in addressing current and foreseeable energy and hydrocarbon feedstock needs. Large portions of natural gas resources are still too expensive to process due to their high content of hydrogen sulfide gas (H2S) mixed with methane, deemed altogether as sub‐quality or "sour" gas. We propose a unique method of activation to form a mixture of sulfur‐containing hydrocarbon intermediates, CH3SH and CH3SCH3, and an energy carrier such as H2. For this purpose, we investigated the H2S‐mediated methane activation to form a reactive CH3SH species by means of direct photolysis of sub‐quality natural gas. Photoexcitation of hydrogen sulfide in the CH4+H2S complex resulted in a barrierless relaxation by a conical intersection to form a ground‐state CH3SH+H2 complex. The resulting CH3SH could further be coupled over acidic catalysts to form higher hydrocarbons, and the resulting H2 used as a fuel. This process is very different from conventional thermal or radical‐based processes and can be driven photolytically at low temperatures, with enhanced control over the conditions currently used in industrial oxidative natural gas activation. Finally, the proposed process is CO2 neutral, as opposed to the current industrial steam methane reforming (SMR).